Multiplexing With Multi-Level ASK and Noncoherent MIMO in Rayleigh Fading - Mallik, Ranjan K. (IEEE transactions on communications, 2024)
For an N_{t} -input N_{r} -output system, noncoherent reception of spatially multiplexed one-sided L-level amplitude-shift keying symbols transmitted over a flat Rayleigh fading channel, with energy detection, is considered. The symbol vector is passed through an N_{t}× N_{t} deterministic precoder matrix. Two precoders are presented: diagonal, having positive diagonal elements in geometric progression (GP); rank-one, having positive row elements in GP. Each symbol vector is transformed into a precoded scalar. For a one-to-one correspondence between integers 0,1,… ,L^{N_{t}}-1 and precoded scalars, a sufficient condition relating the precoder GP ratio ρ to the amplitude levels is derived for each precoder. To ease the difficulty of computing the exact symbol vector error probability (SVEP) for large N_{r} , a Gaussian approximation of the received signal energy is made and a closed form expression for a large N_{r} SVEP approximation is derived. With first level zero, the cases of: levels in arithmetic progression, non-zero levels in GP with amplitude ratio ε , are considered. Parameters ρ and ε are chosen to minimize the SVEP saturation value (approached at high signal-to-noise ratio). Furthermore, symbol-vector-dependent scale factors are introduced for error performance enhancement. Visible light communication and sensor network are two practical application scenarios for this work.